A PROSPECTIVE OBSERVATIONAL STUDY ON PAIN MANAGEMENT IN CANCER PATIENTS AND TELEPHONIC ASSESSMENT OF NAUSEA AND VOMITING (World Journal of Current Medical and Pharmaceutical Research, 2019)
Chemotherapy of cancer has many side effects. Nausea and Vomiting happen to be one of the most common side effects of chemotherapy in cancer patients. One of the most common symptoms seen in cancer patients is pain. It may limit the efficacy of work in daily life activities of the patient. Pain is defined as a highly unpleasant physical sensation caused by “illness or injury”. Nausea is the sensation of being about to vomit. Vomiting or emesis is the expelling of undigested food through the mouth.The aim of this study is to evaluate the pain management in cancer patients and telephonic assessment of nausea and vomiting.This study was conducted with the objective to assess the pain, to evaluate the management of pain in cancer patients, to evaluate the incidence of nausea and vomiting through questionnaires via Telephone, in Care hospitals, Hi- Tech city, Hyderabad. This study is observational in nature and the subjects enrolled under this study were about 116. Informed consent was obtained from all the subjects. Subjects recruited in this study were admitted as in patients in the hospital to receive chemotherapy. The assessment of pain is done by using Visual analogue scale.